IFPRI: Strengthening food and nutrition policies and programs in Bangladesh - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
Bangladesh has made remarkable progress in ensuring food and nutrition security, mainly driven by rapid economic growth and many successful social and health policies and programs. IFPRI has played an important role promoting evidence-based policies and investments that have contributed to Bangladesh’s successes. The Institute’s partnerships with the government and stakeholders will be celebrated at its Bangladesh Country Office Inaugural Ceremony on October 24, 2016 in Dhaka.